Role of Acidic Residues in Helices TH8–TH9 in Membrane Interactions of the Diphtheria Toxin T Domain - Chiranjib Ghatak; Mykola V. Rodnin; Mauricio Vargas-Uribe; Andrew J. McCluskey; Jose C. Flores-Canales; Maria Kurnikova; Alexey S. Ladokhin (Toxins, 2015)
The pH-triggered membrane insertion of the diphtheria toxin translocation domain (T domain) results in transferring the catalytic domain into the cytosol, which is relevant to potential biomedical applications as a cargo-delivery system. Protonation of residues is suggested to play a key role in the process, and residues E349, D352 and E362 are of particular interest because of their location within the membrane insertion unit TH8–TH9. We have used various spectroscopic, computational and functional assays to characterize the properties of the T domain carrying the double mutation E349Q/D352N or the single mutation E362Q. Vesicle leakage measurements indicate that both mutants interact with the membrane under less acidic conditions than the wild-type. Thermal unfolding and fluorescence measurements, complemented with molecular dynamics simulations, suggest that the mutant E362Q is more susceptible to acid destabilization because of disruption of native intramolecular contacts. Fluorescence experiments show that removal of the charge in E362Q, and not in E349Q/D352N, is important for insertion of TH8–TH9. Both mutants adopt a final functional state upon further acidification. We conclude that these acidic residues are involved in the pH-dependent action of the T domain, and their replacements can be used for fine tuning the pH range of membrane interactions.